(untitled) (Global Journal of Management and Business Research, 2018)
This paper classifies the incentives preferred by the Chinese Outward foreign direct investment (OFDI) in Bangladesh. It is mentionable that incentives choice criterion of FDI mostly depends on the socioeconomic condition of the host country, strategies followed by that country with the home country, geographical aspect etc. Elsewhere they try to take advantages from the host country because of them widen market share as well as one of the largest economy in the world. China working with Bangladesh for development FDI is the one initiative. A series of policy incentives, investment sovereignty has been offered to the FDI investors including tax holiday for several years, duty free facility for importing capital machinery, 100% foreign ownership, 100% profit repatriation facility, reinvestment of profit or dividend as FDI, multiple visa, work permit to foreign executives, permanent resident or even citizenship for investing a specific amount, and easy hassle free exit facility. Potential sectors of can attract more FDI are power generation, infrastructure development, private port establishment, joint venture, agro processed product, electrical & electronics, light engineering, and fashion designing etc. After so many incentives offered by the government till now FDI Inflow into Bangladesh is not at a satisfactory level. During last few years fresh FDI investment in not taking place. From the statistics of last few years it is quite clear that, reinvestment of locally earned profit is the major amount of FDI into Bangladesh. Fresh FDI inflow is decreasing day by day. Government has to investigate the issue and undertake necessary measures to increase fresh FDI into Bangladesh.